The Impact of 9/11 on the Media, Arts, and Entertainment
XIX, 254 p.
Keywords: The Impact of 9-11 on the Media, Arts, and Entertainment is the fourth volume of the six-volume series The Day that Changed Everything? This volume's contributors include P.J. Crowley, Mel Dubnick, Nancy Snow, Michèle Cloonan, and other leading scholars.